Congenital Porencephaly and Hippocampal Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs)
MRI volumetric findings were correlated with seizure patterns and EEGs in 14 patients with intractable seizures, porencephaly and hippocampal sclerosis (HS) in a study at the University of Alabama, Birmingham, AL.